Disease mechanism, biomarker and therapeutics for spinal and bulbar muscular atrophy (SBMA). Issue 10 (15th September 2020) - Hashizume, Atsushi; Fischbeck, Kenneth H; Pennuto, Maria; Fratta, Pietro; Katsuno, Masahisa
Abstract : Spinal and bulbar muscular atrophy (SBMA) is a hereditary neuromuscular disorder caused by CAG trinucleotide expansion in the gene encoding the androgen receptor ( AR ). In the central nervous system, lower motor neurons are selectively affected, whereas pathology of patients and animal models also indicates involvement of skeletal muscle including loss of fast-twitch type 2 fibres and increased slow-twitch type 1 fibres, together with a glycolytic-to-oxidative metabolic switch. Evaluation of muscle and fat using MRI, in addition to biochemical indices such as serum creatinine level, are promising biomarkers to track the disease progression. The serum level of creatinine starts to decrease before the onset of muscle weakness, followed by the emergence of hand tremor, a prodromal sign of the disease. Androgen-dependent nuclear accumulation of the polyglutamine-expanded AR is an essential step in the pathogenesis, providing therapeutic opportunities via hormonal manipulation and gene silencing with antisense oligonucleotides. Animal studies also suggest that hyperactivation of Src, alteration of autophagy and a mitochondrial deficit underlie the neuromuscular degeneration in SBMA and provide alternative therapeutic targets.